Pengaruh Pendidikan Kesehatan dengan Audio Visual Terhadap Pengetahuan tentang Covid-19 pada Siswa Kelas 3 SD: The Effect of Health Education with Audio Visual on Knowledge about Covid-19 in Grade 3 Elementary School Students - Valeri Lumongga; Hari Ghanesia Istiani; Sancka Stella (Indonesian Scholar Journal of Nursing and Midwifery Science, 2021)
Introduction: Most of the students knowledge of preventing COVID-19 is still a little less good. One of the effort to break the chain of transmission of the COVID-19 virus is by provoding audio-visual health education. Methods: The research design used Quasi Eksperimental with one-group pre-post test design. The sample taken in this study were 34 respondents who used purposive sampling technique, the instrument used was a questionnaire sheet with a Guttman scale. Results: This study describes the majority of the distribution on knowledge before being given treatment as many as 18 responden (52,9%) lacking knowledge and the frequency distribution of knowledge after being given treatment as many as 18 respondent (52,9%) having good knowledge, this study describes the effect of health education with audio visuals on knowledge of COVID-19 in grade 3 (p = 0,000). Discussion: From the results of the research conducted, it can be concluded that there is an increase in knowledge about COVID-19 after being given audio visual health education.